Accessibility and boarding technology for offshore wind power platforms in China: current status and future prospects - Xichong YU; Jinghong SHANG; Chao LIU; Yufei WU; Yunpeng WANG (You-qi chuyun)
Objective Most offshore wind power platforms are unmanned, resulting in high operation and maintenance costs due to the complex operating environment, limited accessibility, and short time window for going offshore. Consequently, ensuring the safe and efficient transfer of personnel and materials between vessels and wind turbine generators has become a critical challenge in offshore wind power operation and maintenance. Methods Based on the operational context of offshore wind farms in China, the characteristics of five commonly used vessels for offshore wind power operation and maintenance were examined, including monohull, catamaran, trimaran, small waterplane area vessel, and service operation vessel. Then the current status, characteristics and influencing factors of the boarding technologies for offshore wind power platforms were analyzed, including those without motion compensation systems and with wave motion compensation systems, as well as helicopter-assisted boarding. Results Using an offshore wind farm in the South China Sea as a case study, three access options for operation and maintenance were compared and analyzed: catamarans, service operation vessels, and a fixed life support platform adjacent to the converter station. Considering accessibility and costs, it is recommended to adopt the option with a fixed life support platform adjacent to the converter station, supplemented by shuttle carriers for personnel transfer within the wind farm. Conclusion In response to the urgent needs of offshore wind power development and trends in modern science and technology, four key research directions are proposed: (1) boarding technologies and equipment for improved accessibility of far-sea/deep-sea floating wind farms; (2) intelligent operation and maintenance technologies and equipment for offshore wind power; (3) technologies and equipment for boarding using heavy lift drones and loading aircraft; (4) technical standards for boarding and accessibility of offshore wind power platforms. Additionally, leveraging the technical advantages of current electric vertical take-off and landing (eVTOL) aircraft, it is recommended to demonstrate the application of eVTOL in offshore wind farm boarding, operation and maintenance to promote the high-quality development of the entire offshore wind power industry chain.